Difference in Personal Attributes of Entrepreneurship Education Students Based On Level of Study South-West Universities, Nigeria - Oloruntoba, O. A.; Oludipe, B. D.; Adetayo, J. O. (African Journal of Educational Management, 2024)
The study investigated difference in personal attributes of entrepreneurship education students’ based on level of study in Universities in the South-west, Nigeria.The study adopted descriptive survey research design. Multi stage sampling technique was used to select a sample of 274 from 100 level and 316 students in 400 level. Students’ Attitude towards Entrepreneurship Questionnaire (SATEQ, 0.83) and Motivation towards Entrepreneurship Questionnaire (MTEQ= 0.80) were used for data collection. Result showed a significant difference (t= -3.351, p<0.05) in the Entrepreneurial attitude and Entrepreneurial motivation (t= -2.876, p<0.05) of 100 level and 400 level students of entrepreneurship education programme in Universities in the South-West. It was concluded that proper delivery of entrepreneurship education degree programme was a strong factor that enhanced attitude and motivation of students towards entrepreneurial business, hence, it was recommended that public universities should float entrepreneurship education programme because it was found to increase students’ attitude and motivation